In Silico Evaluation Of Curcumin As A Neuroprotective Ligand Targeting Mglur5 - Hazim Arief Halim; Shazwan Abd Shukor; Siti Hanisah Mohd Fuad; Muhammad Fawwaz Shahidi Yaacob; Mohamad Hanief Khalid; Muhamad Arif Mohamad Jamali (Malaysian Society for Molecular Biology and Biotechnology (MSMBB), 2026)
Indexed by ERA / MYCITE